18F-trifluoromethylation of unmodified peptides with 5-18F-(trifluoromethyl)dibenzothiophenium trifluoromethanesulfonate - Verhoog, S; Kee, C; Wang, Y; Khotavivattana, T; Wilson, T; Kersemans, V; Smart, S; Tredwell, M; Davis, B; Gouverneur, V (American Chemical Society, 2018)
The 18F-labeling of 5-(trifluoromethyl)-dibenzothiophenium trifluoromethanesulfonate, commonly referred to as the Umemoto reagent, has been accomplished applying a halogen exchange 18F-fluorination with 18F-fluoride, followed by oxidative cyclization with Oxone and trifluoromethanesulfonic anhydride. This new 18F-reagent allows for the direct chemoselective 18F-labeling of unmodified peptides at the thiol cysteine residue.